Alignment of the strategic, tactical and operational management levels in the public health facilities in Vhembe District, Limpopo Province - Davhana, Bao Keabetswe (My University, 2008)
Health Care System delivery of every country is important for many reasons. Firstly, health services are provided through health systems. Secondly, many countries spend an important share of their national income on health systems. Thirdly, individuals often spend a considerable share of their family income on health. Finally, many health systems do not function as planned as evidenced by the media outcry and dissatisfaction about public health services in particular. Of importance is that the type of Health Care System in a country is strongly related to the historical context in which they have been developed and operated. This was clearly demonstrated as per milestones of the South African Health System. This is also important in describing the transitional pattern and its impact to the current delivery system in provinces and districts. The research study was conducted with the main aim of describing the Strategic Alignment of management levels in Vhembe District. There are seven hospitals in Vhembe District. The researcher interviewed the managers thereof. A literature search was conducted to provide the current "as is" situation and to assist with literature control in the discussion of findings. The literature is silent on what the managers actually do in these institutions. Rather information on what managers have to do floods the literature on Strategic management. A qualitative, exploratory, description and contextual study was conducted. This type of research is conducted in a relatively new area of research which lacks established theories and findings. The interviews were conducted to explore and describe how strategy is aligned in different hospitals. Six themes summarise the findings as follows:• Every hospital has a strategic plan in place. • A specific Strategic planning process is followed and all the hospital managers participate in hospital strategy development. • A specific organogram for all the hospitals in the district exists. • Monitoring process and specific tools are used for this purpose. • National and Provincial Strategic Plans and Performance plans with targets and indicators do not match the resources available to hospitals. • There are challenges relating to what is written on paper compared to what happen at hospital level. The findings cannot be generalized due to the nature of qualitative research approach used in this study. However, the researcher hopes that the study may be repeated in other districts.
Thesis (MBA.) -- University of Limpopo, 2009
Keywords: Health; Health facilities; Public health; Integrated delivery of health care; Public health administration; Hospitals -- Administration; Health services administration -- South Africa